Motivational Factors Influencing the Formation of Rythu Mitra Groups - Manti, Venkataramulu,; Bahal, Ram (Indian Journal of Extension Education, 2011)
Farmer participation is critical to improve the agricultural extension services. Little is known about factors that influence the formation of Rythu Mitra Groups. This paper reports the results of a study in Andhra Pradesh, in which, motivational factors affecting the formation of Rythu Mitra Groups were friends and relatives inspiration, financial problems and influence of extension agents. The study also found that factors inhibiting the formation of Rythu Mitra Groups were lack of information, biases of officials and lack of time.